2017
DOI: 10.1007/978-3-319-62597-3_18
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Education, Including the Use of New Technologies: A Survey of Recent Research

Abstract: This is a summary report of the ICME-13 survey on the theme of recent research in geometry education. Based on an analysis of the research literature published since 2008, the survey focuses on seven major research threads. These are the use of theories in geometry education research, the nature of visuospatial reasoning, the role of diagrams and gestures, the role of digital technologies, the teaching and learning of definitions, the teaching and learning of the proving process, and moves beyond traditional E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
(31 reference statements)
0
11
0
4
Order By: Relevance
“…On the other hand, skills trained in abstract contexts can be applied in different practical contexts. This aim of geometry teaching was confirmed by many authors [23][24][25]. In addition, the authors of [25] also stressed the role of manipulation and the creation of geometrical images in developing the so-called spatial intuitive skills.…”
Section: Results Of the Pre-testmentioning
confidence: 79%
“…On the other hand, skills trained in abstract contexts can be applied in different practical contexts. This aim of geometry teaching was confirmed by many authors [23][24][25]. In addition, the authors of [25] also stressed the role of manipulation and the creation of geometrical images in developing the so-called spatial intuitive skills.…”
Section: Results Of the Pre-testmentioning
confidence: 79%
“…Professional analysis of many publications [19][20][21][22] allows to assert the need for a certain rethinking by teachers of the goals and objectives of teaching geometry at school, and, as a consequence, a certain restructuring of the methodological activities of a teacher of mathematics in teaching geometry to students. Understanding the modern role and place of geometry in the formation and development of the student's personality, readiness and ability to provide appropriate conditions in the learning process of geometry are crucial for the teacher's choice of strategy and tactics of methodological activities [23].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review on geometry education in one of ICME-13 Monographs, Herbst and his colleagues found that there was attention to spatial thinking and to aspects of deductive reasoning from conjecturing to proving across different countries [5] (p. 3). New teaching approaches, such as tool-based task design, inquiry-based learning, and DGS dragging mode, have been applied to teaching secondary school geometry frequently [6]. Meanwhile, it is noted that the traditional Euclidean approaches still existed in the classroom.…”
Section: Introductionmentioning
confidence: 99%